A contemporary archaeology of Londons mega events : from the Great Exhibition to London 2012 - Gardner, Jonathan (UCL Press, 2022)
"Contemporary Archaeology of London's Mega Events explores the traces of London's most significant modern 'mega events'. Though only open for a few weeks or months, mega events permanently and disruptively reshape their host cities and societies: they demolish and rebuild whole districts, they draw in materials and participants from around the globe and their organisers self-consciously seek to leave a 'legacy' that will endure for decades or more. With London as his case study, Jonathan Gardner argues that these spectacles must be seen as long-lived and persistent, rather than simply transient or short-term. Using a novel methodology drawn from the field of contemporary archaeology - the archaeology of the recent past and present-day - a broad range of comparative studies are used to explore the long-term history of each event. These include the contents and building materials of the Great Exhibition's Crystal Palace and their extraordinary 'afterlife' at Sydenham, South London; how the Festival of Britain's South Bank Exhibition employed displays of ancient history to construct a new post-war British identity; and how London 2012, as the latest of London's mega events, dealt with competing visions of the past as archaeology, waste and heritage in its efforts to create a positive legacy for future generations."--